Evaluation of delaminated area of polymer/Carbon Nanotubes fiber reinforced composites after flexural tests by ESPI - Pagliarulo, V.; Palummo, R.; Rocco, A.; Ferraro, P.; Ricciardi, M. R.; Antonucci, V. (2014 IEEE Metrology for Aerospace (MetroAeroSpace), 2014)
In this work, the application of Electronic Speckle Pattern Interferometry (ESPI) is employed for inspecting composite materials subject to thermal load. The composite samples are of interest in the aerospace industry. Through realtime surface illumination by visible laser (i.e. 532 nm), the ESPI technique allows the non-contact, non-destructive, full frame and real time detection of micro-deformations, micro-cracks, residual stress and delamination. The evaluation of the effective delaminated area of damaged polymer/Carbon Nanotubes fiber reinforced composites after flexural tests is presented.